The Relevance of Thematic Hadith Studies of al-Ardh to The Problems of Land Eco-Theology in The Modern Era : Relevansi Kajian Hadis Tematik al-Ardh terhadap Problematika Eco-Teologi Tanah di Era Modern - Asrul; Zahratur Rofiqah Mochamad Sandisi; Achmad Dahlan; Habib Muhammad (Jurnal Living Hadis, 2024)
In the last few decades, serious land issues have emerged, such as land degradation, pollution, land scarcity, and ownership conflicts. Departing from this reality, it is important to examine in depth the concept of land utilization and maintenance, because there has been a shift in the function of land from a medium of production to an economic object. On this basis, two problem formulations are proposed as the starting point of the research. First, how is land discussed in the Prophetic traditions? Second, how is the Prophet's guidance related to the maintenance and utilization of land. Both questions will be approached using a qualitative-descriptive method with a library research approach, namely reading and comparing several references related to the study. The results showed that the study of the term al-ardh in the text of the prophetic traditions led to two findings. First, the philosophical aspect in the form of human attitudes towards land. Second, the technical aspects include the priority of land ownership, land utilization methods, and various functions of land which include theological, ecological, social, and economic functions.